Politics, patronage and scandal at the Provincial Lunatic Asylum, 1848-1857 - Dunlop, Joseph (Ontario History)

(untitled) (The Ontario Historical Society, 2006)
In the mid-nineteenth century, Canada West’s Provincial Lunatic Asylum sat at the heart of a system of patronage. It was this system of patronage that allowed the politician John Rolph to secure the position of Asylum Medical Superintendent for his protégé, Dr. Joseph Workman. However, this same period also witnessed the beginning of a shift away from patronage-based appointments towards a new style of civil service characterized by expertise rather than political or personal connections. Among those who supported this new ideal was the politician and journalist George Brown, who heavily criticized Workman’s appointment as an example of political patronage. Yet, the antagonism that continued to escalate between Brown and Workman owed its genesis not only to Brown’s ideals, but was also fueled by the considerations of party factionalism as well as by the clash of two strong personalities. Their feud would reach its climax in the heavily publicized 1857 libel suit, Workman v. Brown. Sharing a common devotion to the Reform party and to lunacy reform, an examination of the feud between Brown and Workman reveals the many schisms that could divide Reformers during this period.